Optimization of The Durian Peel Waste Adsorbent in The Purification of Used Cooking Oil - Sri Yatmani; Satrio Kuntolaksono; Indri Sivtiani; Windi Novitasari; Ulfah Khairiyyah Luthfiyani (Diponegoro University, 2022)
Durian peel waste (Durio zibethinus Murray) is not effectively exploited and even left to become rubbish, which pollutes the environment. The cellulose from durian peel can be used to generate absorbent activated carbon. This study improves the durian peel adsorbent for the purification of used cooking oil. Carbon activation expands the pores of activated carbon, increasing its surface area and adsorption capacities for purifying spent cooking oil. The best conditions for producing adsorbents from durian peel were identified by adjusting the carbonization period between 300, 400, and 500 °C, activating the 1.25 m mesh size with HCl and KOH activators at concentrations of 3 M and 4 M, and soaking the material for 24 hours. Using 4 M HCl activator, 24 hours at 400 °C, and SNI 06-3730- 1995 criteria, the ideal conditions for activating durian peel activated carbon in the purification of wasted cooking oil were achieved. SEM at 1000-fold magnification (1.357 mm) confirmed an even surface and successful absorption. Durian peel adsorption in the purification of wasted cooking oil reduced peroxides (30.26%), free fatty acids (57.14%), and water content (45%), clarifying the color of leftover cooking oil.